Discretion in Financial Reporting: The Voluntary Disclosure of Compensation Peer Groups in Proxy Statement Performance Graphs* - BYRD, JOHN W.; JOHNSON, MAILYN F.; PORTER, SUSAN L. (Contemporary Accounting Research, 1998)
We examine the 49 Standard & Poor's (S&P) 500 firms that voluntarily disclosed in their 1993 proxy statements, the composition of the comparison group used by each board's compensation committee to set executive compensation policies. We hypothesize that the net benefits of this disclosure are largest when (1) there is a high degree of stakeholder concern about compensation, (2) compensation policies are defensible, and (3) corporate governance is strong. Consistent with our stakeholder concern prediction, disclosing firms have higher compensation levels and are more apt to have received prior shareholder proposals about executive compensation. Contrary to this prediction, we find a negative association between financial press coverage of compensation policies and the probability of disclosure. Additionally, the disclosure decision is unrelated to the defensibility of compensation policies and the firm's corporate governance profile. Industry‐adjusted firm performance, managerial entrenchment, CEO tenure, institutional holdings, and compensation committee independence variables are insignificant. We also compare the financial performance and compensation practices of compensation peers to two yardsticks — performance and pay practices at the sample firms and the corresponding S&P industry index firms. The compensation levels of compensation peers exceed those of the firms in the corresponding S&P industry indexes. Because (1) compensation levels and performance sensitivities at sample firms are more similar to those at compensation peers than to those at S&P industry index firms, and (2) the superior financial performance and higher performance sensitivities of disclosing firms justify high pay, this evidence suggests that the compensation peers of disclosing firms are an appropriate comparison group.